KEMAMPUAN MENULIS PENGALAMAN PRIBADI SISWA KELAS VIII SMP NEGERI 2 KOTA TERNATE - Justam Wahab (Universitas Khairun, 2022)
The problems in this research are (1) What is the improvement of writing ability in the personal experience of eighth grade students of SMP Negeri 2 Ternate City? (2) How is the improvement of writing skills for the eighth grade students of SMP Negeri 2 Ternate City? The research was conducted with the objectives of (1) to find out the results of writing on the personal experiences of eighth grade students of SMP Negeri 2 Ternate City (2) to find out the improvement in the writing skills of eighth grade students of Ternate State Junior High School 2. The method used in this research is descriptive qualitative. The population in this study were 150 students of class VIII SMP Negeri 2 Ternate City. While the sample in this study was 30 students or 50%. Based on the results of the analysis and conclusions, it can be seen that (1) the observations of teachers in the field of Indonesian language studies have carried out the teaching and learning process well in accordance with the implementation of the curriculum and the use of learning tools in the form of syllabus and lesson plans in writing personal experiences; (2) teacher interviews in the field of Indonesian language studies have taught students with personal experience writing learning materials to improve student learning outcomes.